A standard analysis of Egyptian foreign trade structure for wheat - Khalil, Yehia Mohamed Metwally (2021)
There is a positive correlation between the quantity of wheat consumed as a dependent variable and the quantity of imports, local production, real national income, and the population as independent variables. For example, the increase in wheat imports by 1 million tons led to an increase in the quantity consumed by 0.243 million tons; the import equation estimates that the decrease in domestic consumption of wheat by 1 million tons, the import price of wheat by one dollar, and the quantity of wheat stock by 1 million tons each lead to an increase in the quantity of imports of wheat at a rate of 0.97, 0.002, and 0.156 million tons, respectively, while the increase in real national income by 1 billion pounds increases the quantity of imports by about 0.005 million tons.